Conditional Cash Transfers Model of Zakat Distribution for Managing Covid-19 Impact on Health and Education Sectors - Husnul Mirzal (International Journal of Zakat, 2022)
Covid-19 Pandemic affecting negative impact on various sectors, beside its direct impact on increasing the positivity and fatality rate, the pandemic also causes indirect impact on health and education sectors such as increasing in the number of maternal and baby deaths, reducing participation in routine vaccinations, increasing the number of children dropping out of school and decreasing the quality of education. Distribution of social funds using the Conditional Cash Transfers (CCTs) model shows various positive impacts on the health and education sector in several countries, therefore social funds in the form of zakat are very potential to be distributed using CCTs to reduce the Covid-19 Pandemic indirect negative impact. Using a qualitative method with library research approach, researcher aims to offer technical zakat distribution using the CCTs scheme. The distribution of zakat using CCTs to reduce the impact of Covid-19 on health and education can be done by emphasizing mustahiq commitment to education and health facilities. The implementation of CCTs in the distribution of zakat funds can be carried out through several stages, namely recruitment of mustahiq assistants, mustahiq data collection, verification and validation of mustahiq’s data, socialization of commitments, verification of commitment and evaluation of programs and mustahiq’s conditions.